PELAKSANAAN PEMBELAJARAN SENI BUDAYA MATERI MUSIK TRADISIONAL(TALEMPONG PACIK) PADA KELAS X TBSM DI SMK MUHAMMADIYAH 1 PADANG - Carel Oriza Satifa Balqis; Tulus Handra Kadir (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to understand and describe how cultural arts learning takes place at SMK Muhammadiyah 1 Padang. This study is qualitative research with a descriptive approach. The research instruments are the researcher themselves, assisted by writing tools and a camera. Data was collected through literature study, observation, interviews, and documentation. The steps in data analysis include collecting data, reducing data, describing data, and concluding data. The research results indicate that the implementation of cultural arts learning on Traditional Music Material (Talempong Pacik) in Class X TBSM at SMK Muhammadiyah 1 Padang consists of three stages: planning, implementation, and evaluation. In the planning stage, the teacher prepares teaching materials in the form of teaching modules that conform to the Merdeka Curriculum Phase E, and establishes learning objectives that are relevant and contextual to the needs of the students and local character. The implementation stage was carried out through three meetings using methods of lectures, question and answer sessions, demonstrations, and drills. The learning process began with an introduction to the theory and history of Talempong Pacik music, followed by training in basic techniques in groups, culminating in group performances as a form of final performance evaluation. During the teaching process, the teacher managed the class and facilitated learning with a flexible approach, including overcoming limitations in musical instruments through rhythmic simulation via body percussion. At the evaluation stage, not all students achieved the expected competencies, and unfortunately, the follow-up in the form of enrichment for students who had reached their goals or remedial for those who had not succeeded had not been systematically implemented. This certainly impacts students' opportunities to improve or optimally develop their learning outcomes.